2005
DOI: 10.1159/000092417
|View full text |Cite
|
Sign up to set email alerts
|

Scratching below the Surface: Wound Healing and Alanine Mutagenesis Provide Unique Insights into Interactions between Eristostatin, Platelets and Melanoma Cells

Abstract: To study the molecular mechanism of the disintegrin eristostatin, cellular functional studies were performed using ten recombinant alanine mutants. ADP-induced platelet aggregation revealed critical contributions of seven residues within the ‘RGD loop’ (R24, R27, G28, N31) and C-terminus (W47, N48, G49) of this disintegrin. Using an in vitro scratch wound healing assay, four human melanoma cell lines yielded similar results when exposed to wildtype eristostatin. All eristostatin-treated cells healed less of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Many studies have shown that the C-terminal tails of disintegrins are located in the proximity of the RGD loop, the integrin-binding loop, and that the C-terminal regions of disintegrins play synergistic roles in interacting with RGD-binding integrins [16, 18, 20, 21, 25]. For example, C-terminal W67 of flavoridin with an 48 ARGDFP motif is close to D55 [21], C-terminal Y67 of Rho with a 48 PRGDMP motif is close to D55 [25], and C-terminal W67 of trimestatin with a 48 ARGDNP motif is close to P53 [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the C-terminal tails of disintegrins are located in the proximity of the RGD loop, the integrin-binding loop, and that the C-terminal regions of disintegrins play synergistic roles in interacting with RGD-binding integrins [16, 18, 20, 21, 25]. For example, C-terminal W67 of flavoridin with an 48 ARGDFP motif is close to D55 [21], C-terminal Y67 of Rho with a 48 PRGDMP motif is close to D55 [25], and C-terminal W67 of trimestatin with a 48 ARGDNP motif is close to P53 [18].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, eristostatin requires an ARGDW motif and an intact C-terminus (NPWNG) to interact with both platelets and melanoma cells [19]. Eristostatin and bitistatin contain an ARGDWN motif with different C-terminal tails, and eristostatin exhibits a higher affinity to resting platelets [20, 23]. However, the structural basis and mechanism underlying how integrins are recognized by the C-terminus and RGD loop of disintegrins are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…PCR generated 1,071-and 273-bp fragments of the Ob-Rb and Ob-Rt genes, respectively. To ensure that amplification of these genes was within the exponential range, different numbers of cycles (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) were run. Finally, 30 cycles of PCR amplification were chosen.…”
Section: Methodsmentioning
confidence: 99%
“…For example, interaction with integrin a v b 3 affects cell migration, with impact in angiogenesis, tumor metastasis, and atherosclerosis [42,43]. Various disintegrins have been shown to reduce experimental metastasis in melanomas [44,45], and others inhibit endothelial cell adhesion to the extracellular matrix [25]. Thus, the broad pharmacological scope of disintegrins underscores the need for a continuous exploration in search of novel disintegrins and the identification of their targets and pharmacological activities.…”
Section: Introductionmentioning
confidence: 99%